2021
DOI: 10.1101/2021.02.11.430817
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Environmental responsiveness of flowering time in cassava genotypes and associated transcriptome changes

Abstract: Cassava is an important food security crop in tropical regions of the world. Cassava improvement by breeding is limited by its delayed and poor production of flowers, such that cassava flowering under field conditions indirectly lengthens the breeding cycle. By studying genotype and environment interaction under two Nigerian field conditions (Ubiaja and Ibadan) and three controlled temperature conditions (22°C/18°C, 28/24°C and 34/30°C (day/night)), we found that while early flowering genotypes flowered at sim… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…Previous anecdotal evidence suggests that extended photoperiod is more effective at cooler temperatures (Pineda et al, 2020a), and previous growth chamber trials indicated cool temperature is favorable for flowering (Adeyemo et al, 2019;Oluwasanya D. N. et al, 2021). Our results substantiate that cassava breeders aiming to utilize extended photoperiod to produce more flowers would benefit from utilizing locations with cooler temperatures.…”
Section: Effect Of Temperature and Photoperiod On Flower Inductionsupporting
confidence: 83%
See 3 more Smart Citations
“…Previous anecdotal evidence suggests that extended photoperiod is more effective at cooler temperatures (Pineda et al, 2020a), and previous growth chamber trials indicated cool temperature is favorable for flowering (Adeyemo et al, 2019;Oluwasanya D. N. et al, 2021). Our results substantiate that cassava breeders aiming to utilize extended photoperiod to produce more flowers would benefit from utilizing locations with cooler temperatures.…”
Section: Effect Of Temperature and Photoperiod On Flower Inductionsupporting
confidence: 83%
“…Several other regulatory networks have been shown to interact with the SPL/miR172 module and affect the time to flowering, including those involving the plant hormone GA, GI (the core regulatory component of the circadian pathway) (Wang, 2014) and TEMs (Aguilar-Jaramillo et al, 2019). In both field and greenhouse experiments involving temperature, Oluwasanya D. N. et al (2021) found that expression of TEM2 in cassava was consistent with a role in regulating flowering. Our results did not show significant differentially expressed genes related to these pathways but they cannot be ruled out.…”
Section: Temperature Effect On Transcriptomementioning
confidence: 98%
See 2 more Smart Citations